COVID-19 Pandemic: A Qualitative Investigation into the Experiences of COVID Infected Sample of Nepalese People (Journal of Population and Development, 2021)
The main aim of this study is to explore COVID-19 and its experiences of Nepalese people. Primary data were collected through telephone interviews and secondary data were used from different published and unpublished sources in this study. This study is basically based on qualitative data. Total 30 respondents were selected through snowball sampling methods. Among the main three findings, the first is the sources of COVID-19 may or may not be identify and syndromes mayor may not be seen in every individual during first and second wave of COVID-19 .The another conclusion is that the experiences were vary from individual to individual and were felt almost same experiences. However, the duration of recovery days may be different. Lastly, almost all respondents had some kind of experience in post COVID-19 syndromes. But the post COVID-19 side effects have been decreasing slowly. This paper covers only thirty affected respondents’ experiences of residents of Kathmandu. The value of the paper is to inform people about the nature of COVID-19 in various stages.